Stress Analysis of FMIPA UII Students in Practicum Report using Perceived Stress Scale and Robust Regression - Fahma Zuaf Zarir; Edy Widodo; Abdullah Kafabih -; Naufal Fahrezi - (Departemen Statistika Universitas Negeri Padang, 2026)
Higher education requires students not only to master theoretical knowledge but also to apply concepts through practicum activities. At FMIPA UII, the preparation of practicum reports often becomes a source of pressure due to the large number of reports, tight deadlines, and the complexity of data analysis. This study aims to measure students’ stress levels during practicum report preparation using the PSS-10 and to analyze the effects of the number of reports, semester level, and organizational involvement. Primary data were collected from students of all study programs at FMIPA UII through a questionnaire survey. The analysis was conducted using Ordinary Least Squares (OLS) for assumption testing and subsequently robust regression (Huber M-estimation) due to the presence of heteroskedasticity and influential outliers. Descriptive results indicate an average PSS score of 17.95, categorized as moderate stress. However, the robust regression results show that the number of reports, semester level, and organizational involvement do not have a significant effect, either simultaneously or partially, on academic stress. These findings suggest that student stress is more likely influenced by other factors such as time management, coping strategies, social support, practicum design, and overall academic workload.